BOUNDARY ELEMENT SOLUTION FOR INVERSE ACOUSTIC INVOLVING INTERIOR AND EXTERIOR PROBLEM - NOVALINA MANIK , TETTI
The determination of acoustic field due to radiation and scattering has been examined by many researchers in acoustics. Such problem may be called a direct problem. Another case in acoustics is the reverse of the direct problem, where the acoustic parameters such as pressure, particle velocity or acoustic impedance on the source surface are to be determined based on the information of acoustic parameters in the field points. The problem is known as inverse problem. The numerical solution uses in this thesis is Boundary Element Method. The major advantage of this method is the reduction of the dimension of the problem being solved, wherein only the boundary of the surface needs to be discretized. For example, a three dimensional problem may be solved using twodimensional treatment. For axisymmetric sources, the dimension of problem can be further reduced wherein one dimensional treatment. This thesis presents an inverse solution for acoustic radiation and scattering problems involving interior and exterior domains. Formulation for axisymmetric sources is presented for acoustic radiation in interior domain. Test cases are shown involving spherical, cubical and cylindrical bodies for both radiation and scattering problems. The results of the inverse solutions are compared with the true (original) values on source surface in which a good agreement was obtained. Test cases run for several sources give relative error between 0,0045% and 0,0097 % for spherical sources, 0,21% and 0,33% for cubical sources. The results of the axisymmetric formulation for radiation problems give relative error between 0,236% and 0,312% for spherical body for frequency of 163,77 Hz (k = 3 m-1). and between 0,0102 % and 0,0104% for cylindrical body for frequency of 54,59 Hz (k = 1 m-1). Relative errors of scattering problem were obtained between 0,00102% and 0,401% for spherical sources and between 0,0356% and 0,373% for cubical sources for frequency of 54,59 Hz (k = 1 m-1).